Penerapan Sistem Pencatatan Keuangan Aset Biologis Berdasarkan SAK EMKM pada UD Anna Pullet - Febrianti, Erlinda Prastika; Rahma, Fia (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research was conducted with the aim of knowing the application of the biological asset financial recording system according to SAK EMKM at UD Anna Pullet. This study uses qualitative methods with data collection techniques through interviews, documentation and observation. From the results of this study it can be seen that UD Anna Pullet's recording of financial statements and biological assets is still not in accordance with PSAK 69 and SAK EMKM, this occurs due to the owner's lack of expertise in managing financial reports and ignorance of the applicable financial accounting standards so that the owner only records expenses and receipts only. Keywords: Biological Assets, PSAK 69, SAK EMKM